Exploring functional and non-functional requirements of social media on knowledge sharing - Wu, Liming; Che Pa, Noraini; Abdullah, Rusli; Wan Ab. Rahman, Wan Nurhayati; Tee, Mcxin (Asian Research Publication Network, 2016)
Social media (SM) are designed for easily online information sharing and communicating among people, and the sites relate to entertainment, educational and business domains. From requirement elicitation and analysis, social media provide effective communication and sharing on the knowledge and information of system development among stakeholders. This paper aims to identify the relevant functional and non-functional requirements for knowledge sharing (KS), and explore the relationships between the requirements and perceived social media to support knowledge sharing. Hence, a survey was conducted that involve software requirements practitioners in order to gather the requirements on KS. Besides that, partial least squares (PLS) method was used to evaluate the hypothesis and research model. The findings of this study represented that there was a positive and strong relationship between functional requirements and Perceived SM to support requirements knowledge sharing (RKS), however, non-functional requirements has a weak relationship with Perceived SM to support RKS.